Optical detection of the Aharonov-Bohm effect on a charged particle in a nanoscale quantum ring - Bayer, M; Korkusinski, M; Hawrylak, P; Gutbrod, T; Michel, M; Forchel, A (Physical review letters, 2003)
We study spectroscopically the current produced by a charged particle moving in a nanosize semiconductor quantum ring subject to a perpendicular magnetic field. Several Aharonov-Bohm oscillations are observed in the emission of a charged exciton confined in a single ring structure. The magnetic field period of the oscillations correlates well with the size of the rings.